Does Information Affect Online Zakat Payment? - Syahrul Hanafi (International Journal of Zakat, 2020)
Indonesia has enormous potential for zakat, but the results of collecting zakat are still far from the existing potential. OPZ has made various ways to increase the collection of zakat funds, one of which is by implementing online zakat payments. This study aims to analyze the resistance to using online zakat payment services. The research approach is quantitative with the help of smartPLS software. This study's variables consist of information variables, which are independent variables, while the dependent variable consists of traditional barrier variables, image barriers, usage barriers, value barriers, and risk barriers. Data in this study collected using a questionnaire. The sample of this study was 100 respondents from various regions in Indonesia. The results showed that the information has a significant and negative effect on the traditional barrier variables, image barrier, usage barrier, value barrier. This means that the greater / more information provided by OPZ, the barrier in using online zakat payment services are getting smaller / less. The information variable on the risk barrier shows insignificant and negative results.